90.2k views
5 votes
Please help me find the inverse

Please help me find the inverse-example-1
User Shhp
by
4.9k points

1 Answer

3 votes


f^(-1)(x) is supposed to be a function such that


f^(-1)(f(x))=x

In this case, we need


f^(-1)(\sqrt[3]{x-2})=x

To recover
x from
\sqrt[3]{x-2}, we would first need to raise
\sqrt[3]{x-2} to the third power:


(\sqrt[3]{x-2})^3=x-2

Then add 2:


(x-2)+2=x

To recap, we carried out


f^(-1)(\sqrt[3]{x-2})=(\sqrt[3]{x-2})^3+2=x

which implies that the inverse function is


f^(-1)(x)=x^3+2

To verify: we should also have that
f(f^(-1)(x))=x. We get


f(x^3+2)=\sqrt[3]{(x^3+2)-2}=\sqrt[3]{x^3}=x

User Xsznix
by
4.9k points